Tracking SARS-CoV-2 lineage B.1.1.7 dissemination: insights from nationwide spike gene target failure (SGTF) and spike gene late detection (SGTL) data, Portugal, week 49 2020 to week 3 2021 - Borges, Vítor (2022)
We show that the SARS-CoV-2 B.1.1.7 lineage is highly disseminated in Portugal, with the odds of B.1.1.7 proportion increasing at an estimated 89% (95% confidence interval: 83-95%) per week until week 3 2021. RT-PCR spike gene target late detection (SGTL) can constitute a useful surrogate to track B.1.1.7 spread, besides the spike gene target failure (SGTF) proxy. SGTL/SGTF samples were associated with statistically significant higher viral loads, but not with substantial shift in age distribution compared to non-SGTF/SGTL cases.